The carbon cost of impaired welfare on sheep farms - L. Lanzoni; M.C. Reeves; K. Waxenberg; R. Ramsey; A.S. Atzori; J. Bell; R.M. Rees; G. Vignola; C.M. Dwyer (Animal)
In the face of global climate threats, farm and land-management decisions must balance climate concerns with profitability, animal welfare, and ecosystem health. However, few comprehensive studies have quantified the relationship between animal welfare and greenhouse gas (GHG) emissions, and no study focuses specifically on sheep farms. The present study aims to quantify the effects of impaired welfare on GHG emissions for common welfare challenges faced in UK lowland (L) and hill (H) sheep farming systems. Two case study research farms in Scotland, representative of high welfare conditions, were used as baselines for semi-intensive L and extensive H systems. In this study, “high welfare conditions” are defined as situations where animals have access to adequate feeding, suitable housing, good health, and opportunities to express natural behaviours. From each high-welfare baseline, scenarios representing common levels of impaired welfare conditions were modelled, using parameters retrieved from the published literature. The selected poor-welfare scenarios included lameness, gastrointestinal nematodes, blowfly strike, liver fluke, inadequate shelter provision, inadequate feeding during lamb growth and late gestation, and high lamb mortality rate. GHG emissions were estimated “from-cradle-to-farm-gate” using Agrecalc ©, a Life Cycle Assessment tool for the agricultural sector. Total GHG emissions and emission intensities (EI) in kg of CO2 equivalent per kg live weight were compared across the baseline and the scenarios. Gross farm emissions and product-level EIs demonstrated divergent patterns in response to impaired welfare. Most impaired welfare scenarios led to a slight decrease in total farm emissions (0.03–3%), with a few exceptions. On the other hand, EI increased across all impaired welfare scenarios relative to the baseline, because meat production decreased by 1.3–16.6% across all impaired welfare scenarios, reducing resource use efficiency. Lameness was identified as particularly impactful, resulting in 18 and 10% increases in EI on H and L farms, respectively. This was primarily due to the high lamb mortality associated with lameness in published studies. Inadequate shelter provision was associated with an 8–15% increase in EI. Scenarios related to ineffective parasite control contributed to an EI increase ranging from 1 to 13%, while inadequate feeding management caused a 3–4% increase in EI. This study highlights the potential for reducing emission intensity through system-specific interventions, emphasising the importance of integrating animal welfare into GHG mitigation strategies.